Is there a safe place for posterior malleolar screw fixation? An anatomic study on dry bones - May, Hasan (Jt Dis Relat Surg, 2020)
OBJECTIVES: This study aims to determine the secure location and angle of the most distal screw during posterior malleolar (PM) fracture fixation. MATERIALS AND METHODS: This prospective study was performed on September 15, 2019. Distal tibial concave articular depth and PM inclination angle were measured on 100 (50 male and 50 female) dry tibia bones using a digital caliper. A comparative analysis between male and female tibias was performed. RESULTS: Anteroposterior width of male tibia (38.3±3.1 mm) was wider than female tibia (35.3±3.2 mm) (p:<0.001). Mediolateral length of the male tibia (44.8±3.5 mm) was longer than female tibia (42.7±3.4 mm) (p:0.003). Male tibial joint (5.4±0.7 mm) was deeper than that of female (4.7±0.3 mm) (p:<0.001). The PM inclination angle was higher in male tibia (18.0±1.5°) than female tibia (15.4±1.3°) (p:<0.001). CONCLUSION: If a screw placement parallel to the joint surface is desired, the screw insertion should be located 6 mm and 5 mm superior to the distal edge of the PM rim in males and females, respectively. If a more distal screw is required, the screw should be inserted in at least 18° and 15° anterosuperior direction for males and females, respectively.